Perancangan Sistem Informasi Lembaga Sertifikasi Profesi Berbasis web - Syofiah, S; Samudra, Ami Anggraini; Pernanda, Anggri Yulio (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2024)
Professional Certification Institutions are institutions implementing work competency certification activities that obtain a license from the National Professional Certification Agency. Based on type, Professional Certification Institutions are divided into three, namely first party LSP, second party LSP and third party LSP. SMK Negeri 1 Lubuk Basung is a vocational high school that has a license as a First Party Professional Certification Institution (LSP-P1) provider. The assessment process carried out at SMK Negeri 1 Lubuk Basung so far still uses the conventional method, where students come directly to school bringing the requirements, including a photocopy of the Field Practice (PL) certificate, a photocopy of the report card and 2 color 4x6 passport photos to be submitted. to the admin of each department. The creation of this LSP information system was built using the Software Development Life Cycle (SDLC) method with an iterative model as research, and also used Visual Studio Code software, Laragon as a database and Laravel as a framework. This information system is tested with a testing stage divided into 2 types, namely alpha testing (which can be carried out using blackbox testing and whitebox testing) and beta testing (experts and users). the results of beta testing in validation carried out by experts (system experts) obtained an average score of 77.56% with good information, the user assessment questionnaire obtained an average score of 83.93% with very good information.